VanityX: An Agile 3D Rendering Platform Supporting Mixed Reality - Ivan Zoraja; Mirjana Bonkovic; Vladan Papic; Vaidy Sunderam (Applied Sciences, 2023)
VanityX is a prototype, low-level, real-time 3D rendering and computing platform. Unlike most XR solutions, which integrate several commercial and/or open-source products, such as game engines, XR libraries, runtime, and services, VanityX is a platform ready to adapt to any business domain including anthropology and medicine. The design, architecture, and implementation are presented, which are based on CPU and GPU asymmetric multiprocessing with explicit synchronization and collaboration of parallel tasks and a predictable transfer of pipeline resources between processors. The VanityX API is based on DirectX 12 and native programming languages C++20 and HLSL 6, which, in conjunction with explicit parallel processing, the asynchronous loading and explicit managing of graphic resources, and effective algorithms, results in great performance and resource utilization close to metal. Surface-based rendering, direct volume rendering (DVR), and mixed reality (MR) on the HoloLens 2 immersive headset are currently supported. Our MR applications are directly compiled and deployed to HoloLens 2 allowing for better programming experiences and software engineering practices such as testing, debugging, and profiling. The VanityX server provides various computational and rendering services to its clients running on HoloLens 2. The use and test cases are in many business domains including anthropology and medicine. Our future research challenges will primarily, via the MetaverseMed project, focus on opening new opportunities for implementing innovative MR-based scenarios in medical procedures, especially in education, diagnostics, and surgical operations.